2010
DOI: 10.4315/0362-028x-73.10.1907
|View full text |Cite
|
Sign up to set email alerts
|

Control of Bacillus cereus in Foods by Rhodomyrtus tomentosa (Ait.) Hassk. Leaf Extract and Its Purified Compound

Abstract: Edible natural products, either standardized plant extracts or pure compounds, provide unlimited opportunities as safe new antimicrobial agents. This study investigated the antibacterial properties of ethanolic extract from Rhodomyrtus tomentosa (Ait.) Hassk. leaves against Bacillus cereus. Preliminary screening to evaluate the activities of the extract used a paper disc diffusion method against 65 food isolates. The extract produced large inhibition zones in all isolates, ranging from 10 to 18 mm. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…The crude extract produced large inhibition zones (10.00-18.00 mm) against all tested isolates. The study found that the extract could affect both cells and endospores [35] and suggested the use of the extract as a food preservative or food additive agent for controlling the growth of the pathogen and reducing its incidence. It is believed that the extract would not compromise the safety of food.…”
Section: Antibacterial Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…The crude extract produced large inhibition zones (10.00-18.00 mm) against all tested isolates. The study found that the extract could affect both cells and endospores [35] and suggested the use of the extract as a food preservative or food additive agent for controlling the growth of the pathogen and reducing its incidence. It is believed that the extract would not compromise the safety of food.…”
Section: Antibacterial Activitymentioning
confidence: 96%
“…[22] Taraxerol (32) [29] Trans-triacontyl-4-hydroxycinnamate (33) [26] 3,3',4,4'-tetra-O-methylflavellagic acid (34) [26] 3-O-(E)-coumaroyloleanolic acid (35) [26] (-)-(2R,3R)-1,4-O-diferuloylsecoisolariciresinol (36) [26] Arjunolic acid (37) [26] 4-hydroxy-3-methoxybenzoic acid (38) [26] Stigmast-4-en-3-one (39) [26] Oleanolic acid (40) [26] Methyl gallate (41) [26] 3-O-methylellagic acid 4-O-rhamnopyranoside (42) [26] …”
Section: Antifungal Activitymentioning
confidence: 99%
“…The compound was isolated from Rhodomyrtus tomentosa (Aiton) Hassk. leaves and exhibits pronounced antibacterial activity against a wide range of Gram-positive bacteria (Limsuwan & Voravuthikunchai, 2008;Saising et al, 2008;Limsuwan et al, 2009a;Voravuthikunchai et al, 2010;Saising et al, 2011). The MIC and minimum bactericidal concentration values of rhodomyrtone against MRSA range from 0.39 to 0.78 mg ml 21 , which is very close to those of vancomycin (Limsuwan et al, 2009b).…”
Section: Introductionmentioning
confidence: 96%
“…Ethanol extract from R. tomentosa leaves has been demonstrated to exhibit excellent potency against a wide range of Gram-positive bacteria (Limsuwan et al 2009a, b), including food related pathogens such as Bacillus cereus (Voravuthikunchai et al 2010), Staphylococcus aureus (Saising et al 2011), and L. monocytogenes (Odedina et al 2015) at low minimum inhibitory concentrations. The extract also showed the ability to reduce B. cereus viable cells and endospores significantly when applied in precooked rice and tuna steak model (Voravuthikunchai et al 2010). …”
Section: Introductionmentioning
confidence: 99%